(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2019)
The correlation explicitly contained in the title, in reality, is a problem that is subject to serious and sharp opposing discussions, from the foundation and the first theoretical and empirical steps of sociology as a general social science, and especially from the founding of economic sociology as one of the multitude of special sociologies. At the same time, this correlation is a fundamental problem of theoretical and empirical research and of two other special sociologies - the sociology of education and medical sociology. So, the problem of research (theoretical and empirical) is already long defined, the scientific - theoretical and scientific - empirical approaches and research are carried out with a level of frequency that very strongly indicates its social importance. The unanimity and compactness of the findings derived from the scientific - theoretical, and especially the scientific - empirical studies of this correlation, as well as the number of these sociological scientific - theoretical and scientific - empirical studies and findings, all together, with their organic uniqueness and homogeneity, build and radiate the theoretical and empirical research base and framework of a completely real-formed and defined correlation, including as an object of first-degree importance for economic sociology as a special sociology. In reality, this is a double correlation, set up through a kind of interim correlation. Indeed, there is a whole wealth of diverse, including divergent, theoretical points of view and empirically based findings and conclusions that argue and document the social importance and the research theoretical and empirical attraction of these correlations.